2010
DOI: 10.1002/acr.20219
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab therapy for myopathy associated with anti–signal recognition particle antibodies: A case series

Abstract: Objective The myopathy associated with anti-signal recognition particle (SRP) is a severe necrotizing immune-mediated disease characterized by rapidly progressive proximal muscle weakness, markedly elevated serum creatine kinase (CK) levels, and poor responsiveness to traditional immunosuppressive therapies. Reports on the efficacy of B cell depletion therapy for anti-SRP associated myopathy are mixed. We describe eight patients with anti-SRP associated myopathy and their response to treatment with the anti-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(150 citation statements)
references
References 13 publications
4
136
0
10
Order By: Relevance
“…Preliminary observations suggest that B celltargeting therapies, such as anti-CD20, may be efficient in otherwise-treatment-resistant anti-SRP-positive patients (8,41). Since there are very few lymphocytic infiltrates in the muscle of these patients, B celltargeting therapies presumably act on the autoreactive B cell response, which may include antigen presentation to T cells, cytokine production, and/or autoantibody secretion.…”
Section: Evolution Of Anti-srp Levels In Necrotizing Myopathymentioning
confidence: 99%
“…Preliminary observations suggest that B celltargeting therapies, such as anti-CD20, may be efficient in otherwise-treatment-resistant anti-SRP-positive patients (8,41). Since there are very few lymphocytic infiltrates in the muscle of these patients, B celltargeting therapies presumably act on the autoreactive B cell response, which may include antigen presentation to T cells, cytokine production, and/or autoantibody secretion.…”
Section: Evolution Of Anti-srp Levels In Necrotizing Myopathymentioning
confidence: 99%
“…65 Patients with anti-Jo-1, antiMi-2, or anti-SRP antibodies seem more likely to have a response. 66,67 Tumor necrosis factor inhibitors (infliximab, adalimumab, and etanercept) are ineffective and may worsen or trigger disease. 68 Other biologics that may be considered as experimental treatment include alemtuzumab, which is reportedly effective in polymyositis 69 ; anti-complement C3 (eculizumab), which is effective in complement-mediated diseases and may be effective for the treatment of dermatomyositis and necrotizing autoimmune myositis; anti-interleukin-6 (tocilizumab) 70 and anti-interleukin-1 receptor (anakinra), 71 which have been effective in anecdotal cases; anti-interleukin-17; and antiinterleukin-1β (gevokizumab), which is being evaluated in an ongoing trial (EudraCT number, 2012-005772-34).…”
Section: Tr E Atment Of Der M At Om Yositis Polym Yositis a Nd Necrmentioning
confidence: 99%
“…Anti-SRP subjects have unique clinical features, including more severe myopathy with dysphagia, very high CK levels, and better response to steroid therapy [3] . Two recent case series have suggested that anti-SRP levels do correlate with disease severity, and may serve as a marker of poor prognosis [13,14] . Additionally, a recent study identified anti-HMGCoA reductase autoantibodies in 63% of patients with necrotizing autoimmune myopathy [15] .…”
Section: Discussionmentioning
confidence: 99%